Implementasi Latihan Daring Paduan Suara Pada Daerah Terpencil - Nugrahhu, Putra Andino; Aldia Wulandari (Institut Agama Kristen Negeri Palangka Raya, 2024)
Online training is a method of choir training that was widely used during the Covid-19 Pandemic. Many activities are now back to being carried out normally in general, such as choir practice no longer online. This study aims to explain how the application of online choir training can still be carried out under normal circumstances in general. The results showed that online training is still relevant to overcome the problem of long distance. Online rehearsals can help singers learn singing techniques and repertoire. Choir training is a long process and involves many people, the problem of distance which is an obstacle to meet in person with a high intensity of time can be helped by implementing online choir training.